A Comparison of Experimental and Ab Initio Structural Data on Fe under Extreme Conditions - Anatoly B. Belonoshko; Grigory S. Smirnov (Metals, 2023)
Iron is the major element of the Earth’s core and the cores of Earth-like exoplanets. The crystal structure of iron, the major component of the Earth’s solid inner core (IC), is unknown under the high pressures (P) (3.3–3.6 Mbar) and temperatures (T) (5000–7000 K) and conditions of the IC and exoplanetary cores. Experimental and theoretical data on the phase diagram of iron at these extreme PT conditions are contradictory. Though some of the large-scale ab initio molecular dynamics (AIMD) simulations point to the stability of the body-centered cubic (bcc) phase, the latest experimental data are often interpreted as evidence for the stability of the hexagonal close-packed (hcp) phase. Applying large-scale AIMD, we computed the properties of iron phases at the experimental pressures and temperatures reported in the experimental papers. The use of large-scale AIMD is critical since the use of small bcc computational cells (less than approximately 1000 atoms) leads to the collapse of the bcc structure. Large-scale AIMD allowed us to compare the measured and computed coordination numbers as well as the measured and computed structural factors. This comparison, in turn, allowed us to suggest that the computed density, coordination number, and structural factors of the bcc phase are in agreement with those observed in experiments, which were previously assigned either to the liquid or hcp phase.